2012
DOI: 10.1016/j.eururo.2012.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Does Primary Androgen-Deprivation Therapy Delay the Receipt of Secondary Cancer Therapy for Localized Prostate Cancer?

Abstract: Background Despite evidence that shows no survival advantage, many older patients receive primary androgen-deprivation therapy (PADT) shortly after the diagnosis of localized prostate cancer (PCa). Objective This study evaluates whether the early use of PADT affects the subsequent receipt of additional palliative cancer treatments such as chemotherapy, palliative radiation therapy, or intervention for spinal cord compression or bladder outlet obstruction. Design, setting, and participants This longitudinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…Starting in 2003, Gleason 2–4, Gleason 5–6, and Gleason 7–10 corresponded to well, moderately and poorly differentiated. Patients were stratified based on a modification of risk groups utilized by Lu‐Yao et al . Risk group A was stage I–II and Gleason 2–6 (or well or moderately differentiated if Gleason score was not available); risk group B was stage I–II and Gleason 7–10 (or poorly differentiated if Gleason score was not available); and risk group C was stage III with any Gleason score or grade.…”
Section: Methodsmentioning
confidence: 99%
“…Starting in 2003, Gleason 2–4, Gleason 5–6, and Gleason 7–10 corresponded to well, moderately and poorly differentiated. Patients were stratified based on a modification of risk groups utilized by Lu‐Yao et al . Risk group A was stage I–II and Gleason 2–6 (or well or moderately differentiated if Gleason score was not available); risk group B was stage I–II and Gleason 7–10 (or poorly differentiated if Gleason score was not available); and risk group C was stage III with any Gleason score or grade.…”
Section: Methodsmentioning
confidence: 99%
“…Nonetheless, approximately 40% of men >65 yr not treated with RP or RT for localized CaP receive pADT following diagnosis [18]. In the 2 yr following the Medicare Modernization Act of 2003, which led to a 40% decrease in reimbursement for ADT administration, there was a reduction in the inappropriate use of ADT from 38.7% to 25.7% of newly diagnosed localized CaPs [15].…”
Section: Discussionmentioning
confidence: 98%
“…For patients with less aggressive cancers, deferred ADT is safe and reduces the risks of treatment-associated adverse effects, such as osteoporosis, weight gain, decreased libido, decreased muscle tone, diabetes mellitus, and metabolic syndrome. These findings, the fact that primary ADT does not delay the use of secondary cancer therapies, 7 and the fact that randomized clinical trials show no survival benefit, 27 demonstrate that there is a limited role for ADT as primary therapy for men with localized prostate cancer. Health care providers and their older patients should carefully weigh our findings against the considerable adverse effects and costs associated with primary ADT before initiating this therapy in men with clinically localized prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…We have also reported that ADT does not delay the use of secondary cancer therapies and that ADT is associated with an increased risk of fracture and subsequent mortality. 6,7 One of the major limitations of our earlier publication was the limited length of follow-up. 4 To determine whether primary ADT provides a long-term survival advantage, we expanded our study to include more Surveillance, Epidemiology and End Results (SEER) regions and extended the follow-up an additional 6 years, from 2003 to 2009.…”
mentioning
confidence: 97%